2011
DOI: 10.5691/jjb.32.1
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of QIC and CIC for Selecting a Working Correlation Structure in the Generalized Estimating Equation Method

Abstract: The generalized estimating equation (GEE) method is a popular method for analyzing longitudinal data. An inappropriate specification of the working correlation structure reduces the efficiency of the GEE estimation. Pan (2001a) and Hin and Wang (2009) proposed a quasi-likelihood under the independence model criterion (QIC) and a correlation information criterion (CIC) for selecting a proper working correlation structure, respectively. In this study, we proposed modifications to the QIC and CIC using the varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
3
3
0
Order By: Relevance
“…For each simulation setting, the success rates of QIC in selecting the true AR-1 structure for ω Q is approximately twice the success rate of QIC in selecting the true AR-1 structure for ω / . The results obtained for ω Q , were similar to results obtained by Gosho [13] who established success rates of between 32.1% and 72% indicating that the probability of QIC selecting the true AR-1 correlation approached one as…”
Section: Simulation Results On the Consistency Of Qic In Selecting Wosupporting
confidence: 85%
See 3 more Smart Citations
“…For each simulation setting, the success rates of QIC in selecting the true AR-1 structure for ω Q is approximately twice the success rate of QIC in selecting the true AR-1 structure for ω / . The results obtained for ω Q , were similar to results obtained by Gosho [13] who established success rates of between 32.1% and 72% indicating that the probability of QIC selecting the true AR-1 correlation approached one as…”
Section: Simulation Results On the Consistency Of Qic In Selecting Wosupporting
confidence: 85%
“…QIC selection rates established for ω Q are similar to results [1,13] who both established success rates of up to 72% for : 0.5 and m=3 and 4 respectively. However the increase in performance of QIC with increase in in m and : established in the study is dissimilar to results [13] whose indicated that simultaneously increasing m to 8 and : to 0.5 resulted to a slight decrease in the selection rates. The results are further presented in figure 2.…”
Section: Simulation Results On the Consistency Of Qic In Selecting Wosupporting
confidence: 79%
See 2 more Smart Citations
“…For example, what mean‐level covariate effects should be included, should one use GEE2‐NACE or GEE2‐Falconer (we recommend the later due to the potential bias of GEE2‐NACE demonstrated in Section 3.3), and what covariates should one allow heritability to differ by. Several information criteria have been proposed for model selection in GEE‐type models 33‐35 . It would be interesting to try extending these methods to the GEE2‐NACE and GEE2‐Falconer twin models, especially for deciding which covariates affect heritability.…”
Section: Discussionmentioning
confidence: 99%